SUPERVISI KLINIS SEBAGAI STRATEGI PENGEMBANGAN KOMPETENSI PROFESIONAL GURU PAI DALAM MERESPONS ERA ARTIFICIAL INTELLIGENCE - Ismail Anas; M. Nasihuddin (Lembaga Penelitian, Penerbitan dan Pengabdian kepada Masyarakat (LP3M) IAIFA Kediri, 2026)
The development of artificial intelligence has transformed learning practices and requires teachers to serve not merely as content deliverers, but also as facilitators, designers of learning experiences, and guides for the ethical use of technology. This study examines the challenges to teachers’ professional competence in the AI era, the relevance of clinical supervision as a professional development strategy, and its implementation framework for strengthening teachers’ technological adaptability. The study aims to analyze changing professional competency requirements and formulate a conceptual model of AI-adaptive clinical supervision. A qualitative approach was employed through a literature review using a descriptive-analytical systematic literature review design. Data were obtained from regulations, books, national and international journal articles, research reports, and scientific proceedings. The data were analyzed through data reduction, categorization, content analysis, thematic analysis, and conceptual synthesis. The findings indicate that teachers’ professional competence in the AI era should integrate TPACK, AI literacy, critical thinking, digital ethics, and academic integrity. Clinical supervision is highly relevant because it is humanistic, collegial, reflective, and observation-based. Its implementation consists of a pre-observation conference, classroom observation, and a post-observation conference to evaluate the pedagogical effectiveness and ethical appropriateness of AI use. This model can shift school supervision from administrative formality toward teacher-centered professional support.